Numerical simulation of the boundary layer development behind a single quarter elliptic-wedge spire - M. A., Fitriady; Nurizzatul Atikha, Rahmat; A. F., Mohammad; S. A., Zaki (Faculty Mechanical Engineering, UMP, 2023)
For decades wind tunnel has been utilized to generate a quasi-atmospheric boundary layer to observe the wake flow around objects submerged within the Atmospheric Boundary Layer. The quarter elliptic-wedge spire is the most commonly used as a vortex generator among other passive devices. However, despite numerous past studies that utilize rows of spires to generate deep quasi-ABL, only a few researchers targeted spires as the main subject of their investigation. Hence, the present work originally aims to investigate the wake flow structure behind a single quarter elliptic-wedge spire and its aerodynamic interaction with a smooth wall boundary layer. A computational fluid dynamics simulation predicting the wake flow structure behind a single quarter elliptic-wedge spire was conducted using the OpenFOAM® software. The computational domain consists a smooth flat plate, and a single quarter elliptic-wedge spire. A comparison of two Reynolds-Averaged Navier–Stokes turbulence models, namely the k-ɛ model and the SST k-ω model, was conducted. A SIMPLE algorithm was used as the solver in the simulation iteration and ParaFOAM® was used as the post-processing software. The development of the boundary layer height from streamwise x0=0.5S to downwind x0=20S was observed. The mean vertical velocity profiles predicted by both turbulence models are in good agreement with the previous wind tunnel experimental results. However, the results obtained with the k-ɛ model were overpredicted compared to the results of the SST k-ω model causing deviation of the boundary layer height from the wind tunnel experimental data. This anomaly might be caused by the velocity deficit recovery above the boundary layer height region where the turbulence is low.